The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1155/2016/7025793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spontaneous Pneumothorax Surgeries: A 16-Year Experience in Japan

Abstract: Background. Video-assisted thoracoscopic surgery is the surgical procedure of choice for spontaneous pneumothorax due to its noninvasiveness and convenience. A higher recurrence rate with thoracoscopic bullectomy (TB) than that after traditional thoracotomy (TT) led us to adopt thoracoscopic double-loop ligation (TLL) as our standard procedure in 1998. This study compares the effectiveness and safety of these 3 operative procedures. Methods. Patients who underwent their first surgery for spontaneous pneumothor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, we searched and screened 8 articles on the treatment of LAM with thoracoscopic surgery. We meta-analyzed the pneumothorax recurrence rate of LAM in 8 studies [9,[11][12][13][14][15][16] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we searched and screened 8 articles on the treatment of LAM with thoracoscopic surgery. We meta-analyzed the pneumothorax recurrence rate of LAM in 8 studies [9,[11][12][13][14][15][16] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a meta-analysis of 8 case reports and experimental studies [9,[11][12][13][14][15][16] showed that VATS treatment of pneumothorax, the recurrence of pneumothorax was reduced compared with conservative treatment (non-surgical treatment control group) [67/174, 95% CI:-0.44[-0.52,-0.36], P<0.00001], statistics also have research meaning. Among them, I 2 >50% (I 2 =81%), we conducted statistical bias analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Recurrence was detected after VATS in 4% of the patients by Bertrant et al, in 0.4 to 8.6% of the patients by Divisi et al, and in 11.4% of the patients by Chang et al [3,16,17]. There are studies reporting that recurrence rates are higher in patients operated by VATS [11,[18][19][20][21]. Although higher recurrence rates in VATS is based on the differences in pleurectomy techniques in the literature [19,22], Sedrakyan et al reported that the recurrence rate after VATS was significantly lower in the axillary thoracotomy [23].…”
Section: Discussionmentioning
confidence: 96%
“…[10]. According to the results of the studies revealing a high recurrence rate of 16.1 to 16.3% in the patients undergoing bullectomy and the fact that pleurectomy was superior to abrasion and that this could be confined to apical region, there were no patients undergoing only mechanical abrasion in our department [7,11,12]. There are some publications which mention about the fact that postoperative haemorrhage is observed more frequently in apical pleurectomy compared to the other methods, and about the need for reoperation due to haematoma; however, there are no patients who had undergone a reoperation on account of haematoma in our series [13,14].…”
Section: Discussionmentioning
confidence: 99%